Understanding underwater photogrammetry for maritime archaeology through immersive virtual reality - Secci, M.; Skarlatos, Dimitrios; Vlachos, Marinos; Doležal, M.; Liarokapis, F.; Demesticha, S. (My University, 2019)
Underwater archaeological discoveries bring new challenges to the field, but such sites are more difficult to reach and, due to natural influences, they tend to deteriorate fast. Photogrammetry is one of the most powerful tools used for archaeological fieldwork. Photogrammetric techniques are used to document the state of the site in digital form for later analysis, without the risk of damaging any of the artefacts or the site itself. To achieve best possible results with the gathered data, divers should come prepared with the knowledge of measurements and photo capture methods. Archaeologists use this technology to record discovered arteacts or even the whole archaeological sites. Data gathering underwater brings several problems and limitations, so specific steps should be taken to get the best possible results, and divers should well be prepared before starting work at an underwater site. Using immersive virtual reality, we have developed an educational software to introduce maritime archaeology students to photogrammetry techniques. To test the feasibility of the software, a user study was performed and evaluated by experts. In the software, the user is tasked to put markers on the site, measure distances between them, and then take photos of the site, from which the 3D mesh is generated offline. Initial results show that the system is useful for understanding the basics of underwater photogrammetry.
Keywords: Gamification; Underwater archaeology; Underwater photogrammetry; Virtual reality